MicroRNA function in NK cell biology - Beaulieu, Aimee M. (2013)
The important role of microRNAs in directing immune responses has become increasingly clear. Here, we highlight discoveries uncovering the role of specific microRNAs in regulating the development and function of natural killer (NK) cells. Furthermore, we discuss the impact of NK cells on the entire immune system during global and specific microRNA ablation in the settings of inflammation, infection, and immune dysregulation.